Unmasking sin stocks : resolving the anomaly and evaluating its impact on smart-beta performance - Hänel, Paul (2023)
I examine the effect of excluding sin stocks on portfolio returns in the context of smart-beta strategies. Furthermore, this research tries to resolve the sin stock anomaly. My results add to the literature that does not find significant outperformance of smart-beta strategies. I propose a method to extend smart-beta strategies by loading on a set of factors. In this way, investors decrease the risk associated with smart-beta strategies and capture more factor returns. I find smart-beta strategies to have negative spillovers on the loadings of disregarded factors. Next, I show that there is no sin stock anomaly in smart-beta environments. The strategies internalize the anomaly. Finally, I explain the sin stock anomaly with an extension of the Fama-French five factor model. The anomaly is fully captured by loadings on the Fama-French five factor model factors and a betting-against-beta, momentum, and volatility factor. The volatility factor plays a crucial role in explaining the anomaly. Lastly, my study opens avenues for further research in extending the set of factors to further specify the factor loadings. Additionally, future research could aim to extend smart-beta or other trading strategies to capture more of each’s factor returns.